Mediation of AMP Kinase in the Increase of Glucose Uptake in L6 Cells Induced by Activation of Imidazoline I-2 Receptors - Yang, T.-T.; Ku, P.-M.; Hsu, C.-T.; Chung, H.-H.; Lee, W.-J.; Cheng, J.-T. (Hormone and Metabolic Research, 2013)
Recent work using radioactive tracer indicates that activation of imidazoline I2 receptor (I2R) by guanidinium derivatives may increase the glucose uptake in the skeletal muscle. However, the effect of I2R activation on nonradioactive glucose uptake is still unknown. The ability of glucose uptake in cultured L6 cells is then determined using 2-[N-(7-nitrobenz-2-oxa-1,3-diazol-4-yl)amino]-2-deoxyglucose (2-NBDG) as a fluorescence indicator. The changes in 5′-AMP-activated protein kinase (AMPK) expression were also identified by Western blot analysis. In the present study, 2-(2-benzofuranyl)-2-imidazoline (2-BFI) is used to stimulate I2R while 5-aminoimidazole-4-carboxamide-1-β-d-ribofuranoside (AICAR) is applied to activate AMPK directly. Both compounds can increase 2-NBDG in L6 cells in a concentration-dependent manner. Meanwhile, compound C at concentrations sufficient to inhibit AMPK blocked this increase of glucose uptake by 2-BFI or AICAR. However, only 2-BFI-induced glucose uptake action was dose-dependently blocked by BU224, a specific I2R antagonist, in L6 cells. Moreover, AMPK phosphorylation was markedly increased by 2-BFI or AICAR in L6 cells. Similarly, only the effect of 2-BFI was attenuated by BU224 in L6 cells. Thus, we suggest that AMPK is mediated in I2R activation for increase of glucose uptake in the skeletal muscle cell and I2R will be a new target for diabetic therapy.
Keywords: 2-BFI; 5′-AMP-activated protein kinase; BU224; glucose uptake; L6 cell